Investigation of factors that influence belly quality and of cooked bacon characteristics - Goehring, Brandon Lee (Kansas State University, 2015)
One experiment was conducted to determine the collagen and adipocyte characteristics in pork belly fat with different iodine values (IV) and if these factors contribute to belly firmness. An additional two experiments were conducted to create an objective method to score bacon distortion during cooking and to determine how IV and cooking method contribute to bacon distortion. Experiment 1 sorted pork bellies (n=72) into three IV categories: High 76.5 g/100g, Intermediate 70.5 g/100g, and Low 64.9 g/100g. Belly characteristics and firmness were measured before processing into bacon. After processing, 3 bacon slices were selected from the belly and analyzed for histochemistry and collagen analysis. No differences were observed between belly characteristics, while High IV bellies showed softer bellies. Adipocyte characteristics remained unchanged between IV groups. High IV bellies showed greater amounts of collagen. Experiment 2 cooked bacon slices (n=585) on three different appliances (griddle, microwave, and oven) and scored the resulting distortion using a subjective scale. Raw and cooked bacon characteristics were measured to determine which response variables contributing to distortion. Bacon slices were removed from 6 different locations within each belly sampled. Two distortion measurements were created to objectively describe distortion response (crest frequency and bacon distortion index. Subjective distortion scores, crest frequency, bacon distortion index, and raw and cooked bacon characteristics were shown to change between locations of the belly. Accuracy of predictive equations developed to predict distortion scores were low. Experiment 3 evaluated how IV interacts with cooking methodology to influence cooking characteristics, fat quality and distortion of bacon. Bacon slices (n=300) were organized into two IV categories, Low (61.52 to 65.54 g/100g) and High (78.83 to 85.34 g/100g) and cooked using three different appliances (oven, microwave, and griddle). Bacon from the Low IV group had the greatest amount of fat. Cooking bacon on a griddle showed the greatest distortion scores, while the oven produced bacon with the lowest distortion scores. Bacon with higher IV produced bacon with increased distortion scores. Bacon from the High IV group showed smaller cooked dimensions than the Low IV bacon. Neither cooking method nor IV level affected the cooked fatty acid composition.
Keywords: Belly quality; Fat qualityBacon cookery; Animal Sciences (0475)